Impact of Different Trace Elements on the Growth and Proteome of Two Strains of Granulicella, Class “Acidobacteriia” - Costa, Ohana Y. A.; Oguejiofor, Chidinma; Zühlke, Daniela; Barreto, Cristine C.; Wünsche, Christine; Riedel, Katharina; Kuramae, Eiko E. (Frontiers in Microbiology, 2020)
Acidobacteria represents one of the most dominant bacterial groups across diverse ecosystems. However, insight into their ecology and physiology has been hampered by difficulties in cultivating members of this phylum. Previous cultivation efforts have suggested an important role of trace elements for the proliferation of Acidobacteria, however, the impact of these metals on their growth and metabolism is not known. In order to gain insight into this relationship, we evaluated the effect of trace element solution SL-10 on the growth of two strains (5B5 and WH15) of Acidobacteria belonging to the genus Granulicella and studied the proteomic responses to manganese (Mn). Granulicella species had highest growth with the addition of Mn, as well as higher tolerance to this metal compared to seven other metal salts. Variations in tolerance to metal salt concentrations suggests that Granulicella sp. strains possess different mechanisms to deal with metal ion homeostasis and stress. Furthermore, Granulicella sp. 5B5 might be more adapted to survive in an environment with higher concentration of several metal ions when compared to Granulicella sp. WH15. The proteomic profiles of both strains indicated that Mn was more important in enhancing enzymatic activity than to protein expression regulation. In the genomic analyses, we did not find the most common transcriptional regulation of Mn homeostasis, but we found candidate transporters that could be potentially involved in Mn homeostasis for Granulicella species. The presence of such transporters might be involved in tolerance to higher Mn concentrations, improving the adaptability of bacteria to metal enriched environments, such as the decaying wood-rich Mn environment from which these two Granulicella strains were isolated.